Continuous multi-channel sensing of volatile acid and organic amine gases using a fluorescent self-assembly system. Issue 1 (7th December 2018) - Cao, Xinhua; Ding, Qianqian; Li, Yiran; Gao, Aiping; Chang, Xueping
Abstract : A new gelator was designed and synthesized which could detect volatile acid and organic amine in multi-channel. Abstract : A new gelator (1 ) was designed and synthesized through a Knoevenagel condensation reaction between 4-dimethylaminocinnamaldehyde and a gallic acid derivative containing a carbanion. This gelator could form stable organogels in hexane, petroleum ether, DMSO and acetonitrile. The self-assembly processes of1 in four solvents were carefully investigated via UV-vis absorption, fluorescence, FTIR, XRD, water contact angles and field emission scanning electron microscopy (FESEM). Nanofibre and microsphere structures were observed in their self-assembly systems. The xerogel1 film surfaces exhibited different hydrophobicities with water contact angles of 113.5–155°. The J-type aggregation mode was employed in the self-assembly process, and hydrogen bonding and π–π stacking were the main driving forces for organogel formation. Fluorescence emission of organogel1 from acetonitrile was shifted from 558 nm of its corresponding diluted acetonitrile solution to 601 nm with a red-shift of 43 nm. Interestingly, compound1 could sensitively respond to volatile acid, and further to organic amine gases along with obvious color changes. The detection limit for trifluoroacetic acid (TFA) by solution1 in acetonitrile was 1.03 × 10 −8 M with a corresponding association constant ( K ) of 6.85 × 10 4 M −1 . The detection limit for triethylamine (TEA) by solution1 in acetonitrile with 1.8 eq. of TFA was 1.27 × 10 −8 M with a corresponding association constant ( K ) of 4.027 × 10 4 M −1 . The yellow color of solution1 could be reversibly changed to colorless in the titration process. At the same time, xerogel1 exhibited sensitive response abilities for volatile acids and organic amines. The fluorescence of xerogel1 could be quenched when in contact with a volatile acid within 7 s and recovered under further contact with a volatile amine within 15 s. The detection limit of xerogel film1 towards trifluoroacetic acid (TFA) gases was 3.2 ppb. Organogel1 exhibited sensitive response abilities towards TFA and TEA, and then rapidly expressed fluorescence, a gel state and a color change. This research would provide a new window into fast and sensitive detection of volatile acids and organic amines.